Evaluation and validation of Physiological and Operative Severity Score for the enumeration of mortality and morbidity and Portsmouth‐POSSUM scores in predicting morbidity and mortality in patients undergoing head and neck cancer surgeries. Issue 10 (27th July 2020) - Karan, Nupur; Siddiqui, Suhail; Sharma, Kailash S.; Pantvaidya, Gouri H.; Divatia, Jigeeshu V.; Kulkarni, Atul P.
Abstract: Background: Identification of risk factors for perioperative complications helps in the prognostication. We wanted to determine whether Physiological and Operative Severity Score for the enumeration of mortality and morbidity (POSSUM) and Portsmouth‐POSSUM (P‐POSSUM) can be used in patients undergoing head and neck oncosurgery. Methods: We conducted a retrospective analysis of 1265 patients after they had major head and neck oncosurgeries. Demographic, surgical and outcome data was collected. We separately analyzed data for patients who had undergone cancer surgery for oral cavity, pharynx, and larynx. We calculated the POSSUM and P‐POSSUM scores. Results: POSSUM scoring system had moderate discrimination (AUC = 0.61) and good calibration ( P = .36) for the entire study cohort and in the subgroup. Since there were no deaths in the entire cohort, we were not able to check predictive ability of the scores, for mortality. Conclusions: We found that POSSUM had moderate discrimination and good calibration for morbidity prediction in head and neck cancer surgeries, as well as for the selected subgroup.